Restriction of Odd Degree Characters of Sn - Bessenrodt, C.; Giannelli, E.; Olsson, J.B. (Symmetry, Integrability and Geometry: Methods and Applications, 2017)
We study the restriction of odd-degree irreducible characters of the symmetric group Sn.